Incidence of central precocious puberty declines to pre-pandemic levels post COVID-19 pandemic increase: single-center retrospective review in the United States - Vargas Trujillo, Marcela; Rungvivatjarus, Tiranun; Klein, Karen O. (Frontiers in Pediatrics, 2024)
Background and aim of the study: We previously published the increased frequency of new CPP cases during the Covid-19 pandemic in our pediatric endocrinology clinic at Rady Children's Hospital in San Diego, CA, US. We conducted this follow-up study to examine the incidence of new CPP cases requiring treatment with GnRH agonist (GnRHa) in our clinic during 2 years post-pandemic.We performed a retrospective comparison of the number of visits of children newly diagnosed with CPP treated with GnRHa during the 2 years following the first year of Covid-19 pandemic (5/2021-7/2023). We evaluated clinical and bone maturation data as well as differences in timing from diagnosis to onset of treatment.We previously reported in the pre-Covid year, 28 children (1 boy, 27 girls) treated with GnRHa for CPP out of 2,340 new endocrinology visits (1.2% of patients seen). During Covid-19 year, 64 children (7 boys, 57 girls) were treated out of 2,261 new visits (2.8%). The incidence of new CPP cases requiring GnRHa during the pandemic more than doubled compared to pre-pandemic. In the first year post-year 1 of the pandemic (5/2021-4/2022), 46 children (3 boys, 40 girls) started treatment with GnRHa for CPP out of 2,595 new endocrinology visits (1.6% of patients seen). During the second follow-up year (5/2022-4/2023), 22 children (4 boys, 18 girls) started treatment with GnRHa for CPP out of 2,676 new endocrinology visits (0.8% of patients seen).Age at onset of treatment, degree of bone age (BA) advancement, time from diagnosis to onset of treatment, and changes in BMI during the pandemic were not different from prepandemic or post-pandemic.Conclusions: CPP cases requiring GnRHa treatment significantly increased during the first year of the Covid-19 pandemic and then decreased each year post-pandemic. This was not related to BMI, age at diagnosis, degree of bone age advancement, or time from diagnosis to onset of treatment as all these factors have been similar during prepandemic, pandemic, and post-pandemic years. It is reasonable that the postulated hypotheses published regarding the increase during the pandemic would resolve postpandemic.